Family placement breakdowns in Finland - the 1997 Finnish Birth Cohort study - Vuolukka, Kaisa; Vaskivuo, Laura; Ristikari, Tiina; Gissler, Mika; Juutinen, Aapo; Niemelä, Mika (Routledge, 2026)
We used the 1997 Finnish Birth Cohort to study the prevalence of long-term family foster care placement breakdowns. We examined whether and how often placement breakdowns occur among children who have been taken into care and placed in family foster care. We found that half of those who were placed in family foster care had at least one breakdown, 50.6% (n = 173). After family foster care breakdowns, in 43.0% of the breakdown episodes, the children were placed in another foster family; 39.4% of the children entered institutional care or family-style group homes; and the rest of the children entered another type of foster care or home. Our study also showed that placement breakdowns increased when out-of-home placement occurred among those older than 13 years and, most commonly, placement breakdown occurred approximately three years after family placement. In conclusion, it can be stated that placement breakdowns are common in family foster care. Actions ensuring stability and continuity in family foster care are called for.